EFFECTS OF DARK OR OF RED, BLUE OR WHITE LIGHT ON GERMINATION OF SUBTERRANEAN CLOVER SEEDS - Costa, Alexandra; Dias, Alexandra Soveral; Grenho, Maria Gertrudes; Dias, Luís Silva (Emirates Journal of Food and Agriculture, 2017)
Dry or imbibed seeds of the negatively photoblastic burr burying subterranean clover cv. ‘Seaton Park’ were treated with dark or with red, blue or white light to evaluate the effects of light on seed germination. Dry seeds treated with constant white light, red light or blue light during 8 days and subsequently incubated in dark had final germination and duration of germination reduced, and the distribution of germination changed from highly asymmetric to symmetric respectively. Imbibing seeds incubated under constant blue or white light had final germination strongly reduced seven days after sowing (7.3% and 50.1% of the germination under dark) with significant differences between them. After transferral to dark, true complete recovery of germination of seeds treated with white light was observed 19 days after sowing, but only partial recovery in seeds treated with blue light. Results of dry and imbibed seeds are consistent with no activity of phytochromes, as expected in negatively photoblastic seeds. Results of dry seeds are seemingly contradictory because total germination data imply the inactivity of red and blue light photoreceptors, the opposite being implied by duration and shape of germination. A tentative hypothetical solution for the contradiction is presented. Results of imbibed seeds are fully consistent with cryptochromes but not with phototropins mediation of responses to light of seed germination in ‘Seaton Park’. The ecological and adaptive significance of such responses are discussed in the framework of light attenuation in soil and the requirement and ability of subterranean clover ‘Seaton Park’ to bury seeds.